Evaluation of DNA damage in construction-site workers occupationally exposed to welding fumes and solvent-based paints in Turkey - BECEREN, AYFER (SAGE PUBLICATIONS INC, 2010)
In this study, the comet assay was used to evaluate whether welding fume and solvent base paint exposure led to DNA damage in construction-site workers in Turkey. The workers (n = 52) were selected according to their exposure in the construction site and controls (n = 26) from the general population, with no history of occupational exposure. The alkaline comet assay, a standard method for assessing genotoxicity, has been applied in peripheral lymphocytes of all subjects. The mean percentages of DNA in tail (%DNA(T)) of each group were evaluated, including the comparisons between smokers in each different group and the duration of exposure. Significant increase in the mean %DNA(T) (p < 0.01) was observed in all exposed subjects (12.34 +/- 2.05) when compared with controls (6.64 +/- 1.43). Also %DNA(T) was significantly high (p < 0.01) in welders (13.59 +/- 1.89) compared with painters (11.10 +/- 1.35). There was a statistical meaningful difference in % DNA(T) between control and exposed smokers. Our findings indicate that exposure to welding fumes and paints induce genotoxic effect in peripheral lymphocytes, indicating a potential health risk for workers. Therefore, to ensure maximum occupational safety, biomonitoring is of great value for assessing the risk for construction workers.
Keywords: DNA damage; construction site workers; welding fumes; solvent-based paints; comet assay; COMET ASSAY; STRAND BREAKAGE; STAINLESS-STEEL; LUNG-CANCER; CHROMIUM; WELDERS; LYMPHOCYTES; EXPOSURES; MUTAGENICITY; PARTICLES